One Step Sol-Hydrothermal Synthesis of TiO2 Doped with CdS and N for Visible Light Photocatalytic Degradation of Organic Pollutant - Li, Dan; Tong, Haixia; Zhang, Ling (Asian Journal of Chemistry, 2015)
Titanium(IV) oxide photocatalytic oxidation process offers an efficient pollution control technology in environmental protection. However, the weak absorption of TiO2 to visible light limits the application of this catalyst under natural solar illumination. To improve the visible light photocatalytic activity of TiO2, this work developed a one-step sol-hydrothermal method to synthesize CdS and N co-doped TiO2 (CdS/N-TiO2). For comparison, N-TiO2, CdS/TiO2 and two CdS/N-TiO2 namely CdS/N-TiO2A (Cd:Ti:N=1:20:33) and CdS/N-TiO2B (Cd:Ti:N=1:10:17) were synthesized and compared with pure TiO2. The structure and morphology of all these synthesized materials were characterized by X-ray diffraction and scanning electron microscope. The photocatalytic performances of doped TiO2 were investigated by the degradation of Rhodamine B under visible light irradiation. The results indicated CdS/N-TiO2B calcined at 400 °C showed the highest visible light photocatalytic degradation efficiency for Rhodamine B. This catalyst provides a highly effective candidate for removal of bio-refractory organic pollutants using natural solar energy.